Non-lithifying microbial ecosystem dissolves peritidal lime sand - Theodore M. Present; Maya L. Gomes; Elizabeth J. Trower; Nathan T. Stein; Usha F. Lingappa; John Naviaux; Michael T. Thorpe; Marjorie D. Cantine; Woodward W. Fischer; Andrew H. Knoll; John P. Grotzinger (Nature Communications, 2021)
Present et al. examine the processes controlling lithification of microbial mats in a Caribbean peritidal carbonate environment. The authors present sedimentological and geochemical evidence of a surprising bias against preserving the most robust, widespread microbial ecosystems in the sedimentary record.